2018
DOI: 10.1016/j.soilbio.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Decadal-scale litter manipulation alters the biochemical and physical character of tropical forest soil carbon

Abstract: Climate change and rising atmospheric carbon dioxide (CO2) concentrations are likely to alter tropical forest net primary productivity (NPP), potentially affecting soil C storage. We examined biochemical and physical changes in soil C fractions in a humid tropical forest where litter manipulation changed total soil C stocks. We hypothesized that: (1.) low-density soil organic C (SOC) fractions are more responsive to altered litter inputs than mineral-associated SOC, because they cycle relatively rapidly. (2.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 80 publications
3
16
1
Order By: Relevance
“…Previous work at our study site reported minor changes in C density fractions, which were largely equivalent to our results for accessible and mineral-associated SOM based on particle-size fractionation 45 . The seasonal increase in mineral-associated C stocks with litter addition at 0–5 cm depth 45 , indicates only minor changes in soil C storage close to the soil-litter interface.…”
Section: Implications Of the Studysupporting
confidence: 91%
See 1 more Smart Citation
“…Previous work at our study site reported minor changes in C density fractions, which were largely equivalent to our results for accessible and mineral-associated SOM based on particle-size fractionation 45 . The seasonal increase in mineral-associated C stocks with litter addition at 0–5 cm depth 45 , indicates only minor changes in soil C storage close to the soil-litter interface.…”
Section: Implications Of the Studysupporting
confidence: 91%
“…Previous work at our study site reported minor changes in C density fractions, which were largely equivalent to our results for accessible and mineral-associated SOM based on particle-size fractionation 45 . The seasonal increase in mineral-associated C stocks with litter addition at 0–5 cm depth 45 , indicates only minor changes in soil C storage close to the soil-litter interface. Hence, the rapid turnover of mineral-associated SOC at our study site and the lack of changes below 10-cm depth suggest that high biological activity at the soil surface is likely to be a key determinant of SOC storage over decadal time scales.…”
Section: Implications Of the Studysupporting
confidence: 91%
“…Cross polarization spectra were applied with 5,000 scans, a 2 ms contact time, at 12 kHz MAS frequency, and 1.2 s recycle delay. More 13 C NMR analytical details can be found in Cusack et al (2018). Resulting spectra were divided into seven C functional groups, and the relative contributions were quantified by integrating the signal intensities of different chemical shift regions: 0–45 ppm assigned to alkyl C, 45–60 ppm to N ‐alkyl/methoxyl C ( N ‐alkyl), 60–95 ppm to O ‐alkyl C, 95–110 ppm to di‐ O ‐alkyl C, 110–145 ppm to aromatic C, 145–165 ppm to phenolic C, and 165–215 ppm to amide/carboxyl C. The percentages of six biomolecular SOM constituents, including carbohydrate, protein, lignin, lipid, carbonyl, and char, were estimated from the integrated spectra for each sample using a molecular mixing model constrained by C and N concentrations after the acid pretreatment (Table S4) measured by combustion on an elemental analyzer (Baldock, Masiello, Gélinas, & Hedges, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…We quantified SOM associated with four soil particlesize fractions. While we acknowledge that particle size fractionation does not definitively distinguish POM and MAOM, previous studies in the experimental plots demonstrated that particle size fractionation yielded similar results to density fractions (Cusack et al 2018;Sayer et al 2019). Hence, we use the cutoff points for POM vs. MAOM recommended by Lavallee et al (2020) for ease of interpretation, whereby we refer to two size fractions representing POM (2000-200 lm and 200-50 lm) and two size fractions representing MAOM (50-20 lm and \ 20 lm).…”
Section: Particle-size Fractionationmentioning
confidence: 55%